Web-Based Sales Prediction at PT Menara Kudus Indonesia Using the Double Exponential Smoothing Method - Bayu Hidayat, Hilmi; Darmanto, Eko; Supriyono (Jurnal Teknologi Informasi dan Pendidikan, 2025)
PT Menara Kudus Indonesia is a printing, publishing, and bookstore company that still relies on manual sales and paper-based transaction recording, causing inefficiencies and dead stock due to unbalanced production and demand. This study develops a responsive web-based sales prediction system that integrates the Double Exponential Smoothing (DES) method to improve accuracy in forecasting sales trends. The system was developed using the PHP programming language, MySQL database, and the Waterfall SDLC model. The novelty of this research lies in the direct integration of the DES forecasting algorithm into a web-based system, enabling real-time predictions and automated reporting. The implementation results show that the system can process historical sales data, generate accurate forecasts, and provide tabular and graphical reports. The forecast for the 11th month resulted in 174 units, which can serve as a production planning reference. This system improves efficiency, reduces the risk of overstock and understock, and accelerates managerial decision-making.